Model Number Head Together (NHT) dalam Pembelajaran Matematika untuk Meningkatkan Motivasi Peserta Didik Kelas VIIA SMP Negeri 11 Yogyakarta - Pika Merliza; Soedarsono Soedarsono (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2019)
Motivation effect influences students performances in class that can indicate students’ achievement. This Action Research aims to increase motivation towards mathematics learning of seventh graders at SMP Negeri 11, Yogyakarta, Indonesia in 2016/2017 using NHT modal was implemented in two cycles. Data were collected through mathematics motivation questionnaire, observation sheets on teaching and learning process, and field notes. Data were analyzed through qualitative and quantitative analysis. In the first cycle, students’ scores on motivation increased in 88% (good categorization), where three students (9%) in very good motivation level, 19 students (56%) were categorized good, and 12 students (35%) were categorized moderate. The implementation result of NHT in first cycle was 76%. In the second cycle, students’ motivation scores increase beyond exceeded the target. The average results of the motivation score were 93 (good), where was 4 students (12%) in very good categorization, 25 students (73%) were categorized good, and 5 students (15%) were categorized moderate. Then, NHT learning reached 92%. To sum up, it can be concluded that NHT can be alternative modal that can be implemented to help mathematics class for seventh graders at SMP Negeri 11, Yogyakarta, Indonesia.